IMPLEMENTASI PIVOT TABLE UNTUK PENILAIAN BERBASIS CPMK - Katon Wijana; Yetli Oslan; Harianto Kristanto (Fakultas Teknologi Informasi, 2022)
Accreditation is an assessment activity in accordance with predetermined criteria based on the National Higher Education Standards (SNDikti). Graduate competency standards are minimum criteria regarding the qualifications of graduates' abilities which include attitudes, knowledge, and skills stated in the formulation of graduate learning outcomes (CPL). CPL are still general in nature, must be translated into a more specific form, namely course learning achievement achievements (CPMK), each subject must have a CPMK that refers to CPL. In assigning grades to the CPMK, the number of grades entered for each course is different, therefore the CPMK values ​​for each course will be stored in the form of score records. To summarize the CPMK values ​​in the form of rows, a pivot table can be made in the form of columns, but in a university, each study program has a different variety and number of CPMK, therefore it is not possible to create a specific pivot table for the variety. and a certain number of CPMK, so a pivot table must be made that is flexible in terms of variety and amount. In this study, an application program is created that can be used to measure CPL based on learning outcomes for CPMK courses using a pivot table generator so that it can be flexible both in terms of the variety of CPL and the number of CPL study programs.